Duodenal reductase activity and spleen iron stores are reduced and erythropoiesis is abnormal in Dcytb knockout mice exposed to hypoxic conditions - Jeehyea Choi (2018)
Duodenal cytochrome b (Dcytb, Cybrd1) is a ferric reductase localized in the duodenum that is highly upregulated in circumstances of increased iron absorption. To address the contribution of Dcytb to total duodenal ferric reductase activity as well as its wider role in iron metabolism, we first measured duodenal ferric reductase activity in wild-type (WT) and Dcytb knockout (Dcytb -/- ) mice under 3 conditions known to induce gut ferric reductase, dietary iron deficiency, hypoxia, and pregnancy. Dcytb -/- and WT mice were randomly assigned to control (iron deficiency experiment, 48 mg/kg dietary iron, hypoxia experiment, normal atmospheric pressure, pregnancy experiment, nonpregnant animals) or treatment (iron deficiency experiment, 2-3 mg/kg dietary iron, hypoxia experiment, 53.3 kPa pressure, pregnancy experiment, d 20 of pregnancy) groups and duodenal reductase activity measured. Wefound no induction of ferric reductase activity in Dcytb -/- mice under any of these conditions, indicating there are no other inducible ferric reductases present in the duodenum. To test whether Dcytb was required for iron absorption in conditions with increased erythropoietic demand, we also measured tissue nonheme iron levels and hematological indices in WT and Dcytb -/- mice exposed to hypoxia. There was no evidence of gross alterations in iron absorption, hemoglobin, or total liver nonheme iron in Dcytb -/- mice exposed to hypoxia compared with WT mice. However, spleen nonheme iron was significantly less (6.7 ± 1.0 vs. 12.7 ± 0.9 nmol mg tissue -1 , P < 0.01, n = 7-8) in hypoxic Dcytb -/- compared with hypoxic WT mice and there was evidence of impaired reticulocyte hemoglobinization with a lower reticulocyte mean corpuscular hemoglobin (276 ± 1 vs. 283 ± 2 g · L -1 , P < 0.05, n = 7-8) in normoxic Dcytb -/- compared with normoxic WT mice. We therefore conclude that DCYTB is the primary iron-regulated duodenal ferric reductase in the gut and that Dcytb is necessary for optimal iron metabolism. © 2012 American Society for Nutrition.